2022
DOI: 10.3390/antiox11081508
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin Prevents Chronic Alcoholic Injury by Regulating Redox Balance and Lipid Metabolism in Female C57BL/6J Mice

Abstract: This study aimed to investigate the preventive effects of lactoferrin (Lf) on chronic alcoholic liver injury (ALI) in female mice. Female C57BL/6J mice were randomly divided into four groups: control group (CON), ethanol administration group (EtOH), low-dose Lf treatment group (LLf), and high-dose Lf group (HLf). In the last three groups, chronic ALI was induced by administering 20% ethanol ad libitum for 12 weeks. Mice in the CON and EtOH groups were fed with AIN-93G diet. Meanwhile, 0.4% and 4% casein in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Further, the Lf treatment could reduce ethanol-induced cytotoxicity and intracellular ROS accumulation (Figure 3). Similar to the animal experiments [5][6][7], Lf also exhibited preventive effects on ALI in vitro.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Further, the Lf treatment could reduce ethanol-induced cytotoxicity and intracellular ROS accumulation (Figure 3). Similar to the animal experiments [5][6][7], Lf also exhibited preventive effects on ALI in vitro.…”
Section: Discussionsupporting
confidence: 77%
“…Our previous studies have confirmed that Lf can prevent ALI in mice, and the mechanisms are associated with hepatic redox homeostasis regulation [5][6][7]. Nuclear factor E2-related factor 2 (Nrf2) is a central regulator for redox balance, and our animal experiments highlighted the key role of Nrf2 in Lf-mediated ALI prevention [6,7]. Besides our studies, other research groups have also indicated that Lf treatment is linked to Nrf2 activation in different organs or cells [8][9][10][11].…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…A study found that ethanol can promote fatty acid synthesis, which is characterized by signi cant upregulation of the protein expression of ACC and FAS 22 . Simultaneously, ethanol also reduced the protein level of CPT1A, a key enzyme of fatty acid β-oxidation 23 . Some studies have also found that ethanol can promote the uptake of more fatty acids by hepatocytes 24 .…”
Section: Discussionmentioning
confidence: 95%
“…In addition, our results indicated that hesperidin may play a protective role in bMECs through the Keap1/Nrf2/ARE signaling pathway. The Keap1/Nrf2/ARE signaling pathway is a key regulator of cellular antioxidant defense [ 44 , 45 ]. Keap1 is a negative regulator of Nrf2 that binds to Nrf2 and retains it in the cytoplasm [ 46 ].…”
Section: Discussionmentioning
confidence: 99%